Notes on Phyllanthera (Apocynaceae) from the upper Sepik of Papua New Guinea: P. lancifolia and P. piforsteriana sp. nov. - Takeuchi, Wayne (Phytotaxa, 2014)
Phyllanthera piforsteriana (Apocynaceae) is described from the Sepik River basin in Papua New Guinea. Distributional notes are also provided for P. lancifolia, a frequent associate of the new species but otherwise rarely represented in herbarium collections.